PENGARUH IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH TERHADAP PARTISIPASI MASYARAKAT DI KOTA SUKABUMI - Khairunnisa Alya Puspita; Ike Rachmawati; Hegia Sampurna (Kebijakan : Jurnal Ilmu Administrasi, 2023)
Policy implementation is a policy process that involves the several actor, one of which is citizen. Citizens participation turn out to the success and accuracy affecting factors of policy to achieving goals. However, the enacthment of waste management policy in Sukabumi City has not given a result in the amount of waste decrease in every year. It could be due to implementations affecting to citizens participation. Afterwards, there are gap between two results in previous researches related to the influence of waste management policy implementation on public participation which it need more research. This research aims to known the waste management policy implementation in Sukabumi City, Citizens participation on waste management in Sukabumi City, and the influence of policy implementation and Citizens participation in Sukabumi City. George Edward Theory used to quantify the policy implementation, there are 4 dimension inculdings communication, resources, disposition, and bureaucratic structure. Meanwhile Citizens Participation used Keith Davis Theory, there are 3 idea inculdings mental and emotional involvement, motivation to contribution, and responsibility. This resarched used quantitative by distributing questionnaries to the public. As for the number of samples are 100 respondents which is devided into 7 Sukabumi City Districts. The questionnaries are valid and reliable. The result of this research are the waste management policy implementation and Citizens participation have high categorized. Then, there is the influence of waste management policy implementation based on communication, resources, disposition, and bureaucratic structure on Citizens participation with 14.8% of R2.   Keywords: Policy Implementation, Citizens Participation, Waste Management, Sukabumi City.